Prevalence of Deep Vein Thrombosis in Postoperative Patients Using Risk Assessment Card: An Observational Study - Dr. Katti Ravi Kumar; Dr Kari Veerabhadra Swamy; Dr. Mude Sarala; Dr Megavath Motilal (International Journal of Pharma and Bio Sciences, 2023)
Venous thromboembolism (VTE) is a medical condition where blood coagulation happens most frequently in the veins of the limb, crotch, or arm. The most dreaded complication of deep vein thrombosis (DVT) is pulmonary embolism (PE), possibly lethal. The incidence of VTE in India was 17.46 per 10,000 hospital admissions. Given the high incidence, the current study was undertaken. The present study was done with the aim to know the prevalence of administration of prophylaxis of DVT in postoperative patients using a risk assessment card at a tertiary care centre named Siddhartha Medical College, Vijayawada, Andhra Pradesh, in India. Objectives of the study include studying the impact of DVT risk assessment cards on the prevalence rates of prophylaxis administration in postoperative patients and establishing the current rates of thromboprophylaxis in post-operative surgical patients. This observational study was done on 60 patients scheduled for various surgeries from July 2020 to December 2022. 60 patients were randomized into groups: A and B, each containing 30 patients, depending on the phase. Group A (Phase 1) included patients before introducing the risk assessment card for DVT. Group B (Phase II) included patients after introducing the risk assessment card for DVT. Results showed that most patients in both study phases were aged below 40 years. Most of the patients were males. Most of the patients belonged to the low-risk category. The two groups have no significant difference in the mean risk score. Mechanical and drug prophylaxis incidence was significantly higher in group B or phase II patients. Introducing risk assessment cards for DVT for Inpatient (IP) case sheets was an effective and cost-effective way of improving overall prophylaxis for DVT.